PENGARUH VARIAN NILAI SAHAM, KEPEMILIKAN PUBLIK, DAN DEBT TO EQUITY RATIO PADA PRAKTIK PERATAAN LABA - Susanta Putra, Rizky Anggriawan; Suardana, Ketut Alit (E-Jurnal Akuntansi; Vol 15 No 3 (2016), 2016)
The income smoothing and the factors that influence it is very important in order to avoid asymmetries of information and a medium toassess the performance management of a company. There are several factors that influence the practice of income smoothing variance value of the shares, public ownership, and debt toequity ratio. The population in this study are all companies listed on the Indonesia Stock Exchange during 2010-2013. The population in this study are all banking companies listed in Indonesia Stock Exchange during 2010-2013. The number of samples used in this study is the 128th. Data analysis techniques used to solve these problems is the multiple regression analysis. Based on the results of analysis known that public ownership and debt to equity ratio influence the practice of income smoothing manufacturing company in Indonesia Stock Exchange during 2010-2013.While variance value of the shares does not influence the practice of income smoothing manufacturing company in Indonesia Stock Exchange during 2010-2013.
Keywords: income smoothing, variance value of the shares, public ownership, debt to equity ratio